Functional Rehabilitation with an Onlay Ceramic Adhesive Restoration: Case Report - Ramírez Barrantes DDS, MSD, PhD, Juan Carlos (2019)
The objective of this article was to analyze the indications for the proper selection of  Onlay adhesive ceramic restorations, providing a step-by-step clinical protocol. Biomechanical principles based on morphological considerations and geometric terms must be present for the careful preparation of Onlay-type cavities. Concepts about cavitary preparations are discussed under essential conditions in the preservation of healthy dental tissue, without compromising the functional and aesthetic results over time. The author's suggestion is to respect and follow in a timely manner each of the steps applied in this restorative clinical protocol, to improve the final outcome of the restoration.